An efficient method for synthesis of some heterocyclic compounds containing 3-iminoisatin and 1, 2, 4-triazole using Fe3O4 magnetic nanoparticles. (4th May 2017) - Nami, Navabeh; Zareyee, Daryoush; Ghasemi, Maryam; Asgharzadeh, Ameneh; Forouzani, Mehdi; Mirzad, Somayeh; Hashemi, S. Milad
ABSTRACT: 1, 2, 4-triazole derivatives were prepared by reaction of thiocarbohydrazide and some esters in 60% ethanol. Condensation of 1, 2, 4-triazole derivatives with isatin gave Schiff bases of 3-iminoisatin derivatives. Reaction of malonic or succinic acid dihydrazide with isatin lead to formation of N, N' -bis-(3-imino-1, 3-dihydro-indolyl-2-one)-malonamide8a and N, N' -bis-(3-imino-1, 3-dihydro-indolyl-2-one)succinamide8b in good yields under mild reaction conditions. These reactions are catalyzed by Fe3 O4 MNPs. The chemical structures were confirmed by Fourier transform-infrared, 1 H-NMR, 13 C-NMR, gas chromatography-mass spectrometry spectroscopy, and elemental analysis. GRAPHICAL ABSTRACT: